+0

# Determine the average rate of change of the function between the given values of the variable.

0
446
10
+253

A function is given. Determine the average rate of change of the function between the given values of the variable.

f(t) =

f(t) = 7/t;    t = a, t = a + h
sally1  Jun 16, 2014

### Best Answer

#8
+26399
+10

I suspect sally1 is expecting this to be taken just a little further, so taking up where Melody left off:

(f(a+h) - f(a))/h = (7/(a+h) - 7/a)/h

= (7a - 7(a+h))/(a*(a+h)*h)

= -7h/(a*(a+h)*h)

= -7/(a*(a+h))

Alan  Jun 17, 2014
Sort:

### 10+0 Answers

#1
+91448
+10

If t is on the horizinal axis and f(t) is on the vertical axis (which is normal)

f(t) = 7/t;    t = a, t = a + h

f(a)=7/a

f(a+h)=7/(a+h)

The time difference between time=a and time=a+h is a+h-a=h (this is the horizonal difference)

f(a+h)-f(a) is the vertical difference

the average rate of change of the function is the

(difference between the function values at the end points)/(difference in time)

Like speed = distance/time OR

like the gradient of a line where A and B are two point on the line

=(difference between the y values  /difference in the x values )

Average rate of change= [f(a+h)-f(a)]/h

Melody  Jun 16, 2014
#2
+253
+5

I am confused. Why aren't there any numbers or letters?

sally1  Jun 17, 2014
#3
+91448
+10

Because you were only given a's and h's .

would you like me to make up some numbers? (only joking)

would you like me to try and draw you a graph?

Melody  Jun 17, 2014
#4
+253
+5

It keeps coming up as incorrect. That's why I am so confused. But I do understand how you got your answer...because there isn't anything else left.

sally1  Jun 17, 2014
#5
+91448
+5

This  is the introduction to calculus

See if this picture helps

Melody  Jun 17, 2014
#6
+91448
0

what does your answer come up as?

Melody  Jun 17, 2014
#7
+4145
0

Its a mystery.............

zegroes  Jun 17, 2014
#8
+26399
+10
Best Answer

I suspect sally1 is expecting this to be taken just a little further, so taking up where Melody left off:

(f(a+h) - f(a))/h = (7/(a+h) - 7/a)/h

= (7a - 7(a+h))/(a*(a+h)*h)

= -7h/(a*(a+h)*h)

= -7/(a*(a+h))

Alan  Jun 17, 2014
#9
+253
0

Alan's answer was correct. So I suppose I put both your answer and his answer together?

sally1  Jun 17, 2014
#10
+91448
+5

Yes that is correct - Alan manipulated my answer to get the simplified answer that you wanted.

Melody  Jun 18, 2014

### 3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details